Passenger Transport Trends in the V4 Countries - Komorousová Veronika; Hinke Jana (Logi, 2023)
Passenger transport, or efforts to modify it in order to minimize its negative environmental impact, is a discussed issue. This paper aims to assess the trends in passenger transport indicators in the V4 countries between1995 and 2018. Within the time series of indicators, the transport indicators of individual car transport is analyzed and compared with the public mass transport broken down into rail, bus, tram, and underground transport. The results show a clear upward trend in individual car transport performance, while rail passenger transport performance shows a convex quadratic trend in all V4 countries except Hungary. In contrast, bus transport tends to show a downward trend. CO2 emissions and traffic accidents tend to decrease in the majority of the V4 countries, despite the increasing performance of individual car transport, which is a very positive finding that corresponds with the commitments of all V4 countries, or with social responsibility.